2002
DOI: 10.1017/s135583820202633x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of translation by RNA–small molecule interactions

Abstract: Small molecule ligand-RNA interactions have the potential to influence gene expression at a variety of steps and in a number of ways. Here, we demonstrate that such interactions are sufficiently stable to inhibit translation of eukaryotic mRNAs in vitro and in vivo. Inhibition is only observed when the 59 UTR of the mRNA is targeted, and the response is proportional to the number of binding sites within this region. We find that small molecule ligand-RNA interactions can be sufficiently stable to prevent 80S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
80
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 33 publications
6
80
1
2
Order By: Relevance
“…However, there are only a few aptamers that have been reported that act as a riboswitch in vivo (Werstuck and Green 1998;Grate and Wilson 2001;Harvey et al 2002;Hanson et al 2003). In a previous study, we have shown that only 1 of 15 different tetracycline-binding aptamers is able to mediate ligand-dependent regulation of gene expression .…”
Section: Combining In Vitro Selection and In Vivo Screening Creates Amentioning
confidence: 95%
See 1 more Smart Citation
“…However, there are only a few aptamers that have been reported that act as a riboswitch in vivo (Werstuck and Green 1998;Grate and Wilson 2001;Harvey et al 2002;Hanson et al 2003). In a previous study, we have shown that only 1 of 15 different tetracycline-binding aptamers is able to mediate ligand-dependent regulation of gene expression .…”
Section: Combining In Vitro Selection and In Vivo Screening Creates Amentioning
confidence: 95%
“…However, the majority of in vitro selected aptamers display no regulatory activity in vivo. Up to now, only five small molecule-binding aptamers have been identified that have the potential to act as riboswitches (Werstuck and Green 1998;Grate and Wilson 2001;Harvey et al 2002;Suess et al 2003). In addition, two of these-namely, the theophylline and the tetracycline aptamer-have been used as a binding domain for the engineering of more complex riboswitches with broadened functions and applicability (Buskirk et al 2004;Desai and Gallivan 2004;Isaacs et al 2004;Suess et al 2004;Bayer and Smolke 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, whereas many in vivo applications of artificial riboswitches in both prokaryotes and eukaryotes have been reported thus far (Werstuck and Green 1998;Grate and Wilson 2001;Harvey et al 2002;Suess et al 2003Suess et al , 2004Desai and Gallivan 2004;Kim et al 2005;Nomura and Yokobayashi 2007;Weigand and Suess 2007;Win and Smolke 2007;Ogawa and Maeda 2008a;Wieland and Hartig 2008;Weigand et al 2008), there have been few examples of their applications as in vitro biosensors. I and Maeda have previously reported two types of prokaryotic riboswitch-based in vitro biosensors that were rationally designed using aptazymes, which are functional RNA and cleave themselves in response to their specific ligand molecules (Ogawa andMaeda 2007, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…I therefore have decided to establish a method for rationally constructing pt-ON-riboswitches in vitro by the use of aptamers without ribozymes. Moreover, I chose to design eukaryotic ribozymefree aptamer-based pt-ON-riboswitches because there has been no example of those obtained, even via selection methods, in contrast to prokaryotic ribozyme-free aptamer-based pt-ON-riboswitches selected in vivo (Desai and Gallivan 2004;Nomura and Yokobayashi 2007;Muranaka et al 2009) or eukaryotic ribozyme-free aptamer-based pt-OFF-riboswitches (down-regulation-type) (Werstuck and Green 1998;Grate and Wilson 2001;Harvey et al 2002;Suess et al 2003;Kim et al 2005;Weigand and Suess 2007;Weigand et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A related approach that involves embedding RNA 'aptamers' at sensitive parts of mRNAs would achieve similar goals. [19][20][21][22][23][24] These ligand-binding RNAs could be used to control genes for basic research purposes, and also could be useful as in vivo sensors for natural metabolites. Furthermore, tailor-made RNA switches should empower researchers to deliver gene products using expression constructs with nonintrusive genetic control systems modulated by specific compounds.…”
mentioning
confidence: 99%